The Role of Brand Preference as Moderation in the Relationship between Social Media Influencer, Brand trust, and Purchase Intention - Nadia Nadia; TN Anisah; Eni Andari (International Journal of Economics (IJEC), 2023)
This study aims to examine whether an individual's preference for their favorite influencer can strengthen their awareness of the advertised product and ultimately increase their purchase intention. A total of 270 samples were used in this study, following specific criteria. The data were analyzed using IBM SPSS Statistics 16 and AMOS ver.22. The results of the study indicate that the presence of celebrity influencers is effective in creating consumer awareness, especially among their followers. Furthermore, the higher the awareness of the brand being advertised, the higher the potential purchase intention. Further findings from the study demonstrate that celebrity preference moderates the influence of social media influencers on Brand trust.